Gender and age-related differences in depressive symptoms and health behaviors among Mexican youth - Raffaelli, Marcela; Andrade, Flavia Cristina; Poppe, Emilia M.; Sanchez-Armass, Omar; Vazquez Vidal, Itzel; Aradillas Garcia, Celia (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2013)
Gender- and age-related differences in, and behavioral health correlates of, depressive symptoms were examined in 5152 Mexican university applicants aged 16-21 (55% female). Participants self-reported depressive symptoms (CESD-10) and health behaviors (smoking, alcohol use, physical activity). Overall, and from ages 17 to 20, significantly more female than male respondents met the cut-off for depression (CESD-10 scores ≥10). Logistic regressions controlling for age and parental education indicated that depressed young women were 82% more likely to smoke and 20% less likely to exercise than their non-depressed peers; depressed young men were 30% more likely to drink than non-depressed males. Findings extend knowledge on the developmental course and health consequences of depression by examining these processes in an international setting.